2009
DOI: 10.1128/aem.00708-09
|View full text |Cite
|
Sign up to set email alerts
|

Negative Roles of a Novel Nitrogen Metabolite Repression-Related Gene, TAR1 , in Laccase Production and Nitrate Utilization by the Basidiomycete Cryptococcus neoformans

Abstract: The multicopper oxidase laccase is widespread in fungi and has great industrial importance. One puzzle regarding laccase production in the basidiomycetous yeast Cryptococcus neoformans is that it is inhibited by high temperature (e.g., 37°C). In this paper, we report identification of a nitrogen metabolite repression-related gene, TAR1, which is responsible for laccase repression. Disruption of TAR1 results in a significant increase in the level of LAC1 mRNA at 37°C. The putative protein Tar1 shares a moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 36 publications
(47 reference statements)
0
37
2
Order By: Relevance
“…Genes encoding homologs of key catabolic enzymes for cadaverine, nitrate, and nitrite utilization were also not found in the genome of VNI strain H99 via BLASTp analysis, explaining the lack of growth on these nitrogen sources. We are therefore unable to explain the Cryptococcus growth phenotype associated with nitrate utilization that was observed by Jiang et al; consistent with our bioinformatic analyses, none of the 16 Cryptococcus strains tested were able to utilize nitrate or nitrite as the sole nitrogen source ( Jiang et al 2009). …”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Genes encoding homologs of key catabolic enzymes for cadaverine, nitrate, and nitrite utilization were also not found in the genome of VNI strain H99 via BLASTp analysis, explaining the lack of growth on these nitrogen sources. We are therefore unable to explain the Cryptococcus growth phenotype associated with nitrate utilization that was observed by Jiang et al; consistent with our bioinformatic analyses, none of the 16 Cryptococcus strains tested were able to utilize nitrate or nitrite as the sole nitrogen source ( Jiang et al 2009). …”
Section: Resultsmentioning
confidence: 54%
“…The Nmr proteins are inhibitors of the functions of A. nidulans AreA and N. crassa Nit2, and a potential homolog of this protein named Tar1 has recently been characterized in C. neoformans, suggesting that the regulation of GATA factor activity may operate in a similar fashion to these filamentous ascomycetes (Pan et al 1997;Andrianopoulos et al 1998;Jiang et al 2009). However, this model is confounded by conflicting observations between the studies of Jiang et al and our own.…”
Section: Discussionmentioning
confidence: 99%
“…This ability to use nitrate is less frequent in strains of the C. neoformans species. While these results conflict with the prevailing understanding of nitrate nonutilization by all pathogenic Cryptococcus species, they do confirm the published results of Jiang and colleagues showing a latent ability of pathogenic cryptococci to utilize nitrate as the sole nitrogen source (13). Furthermore, we confirmed the accepted paradigm that nonpathogenic species, such as Cryptococcus albidus, display robust growth on nitrate (data not shown).…”
Section: Discussioncontrasting
confidence: 37%
“…Mechanistically, Wilson and colleagues showed in Magnaporthe that control of nitrogen metabolism and pathogenicity was integrated with trehalose metabolism; Tps1 is required for proper regulation of the nitrogen repressor NMR1 (12). The latter finding is intriguing, as recent data regarding the NMR1 homolog TAR1 in C. neoformans demonstrate the relationship of nitrogen regulation to melanin production, which is a major virulence factor for C. neoformans (13), and the trehalose pathway has signal control on the cryptococcal virulence composite (14,15).…”
mentioning
confidence: 92%
“…Although it was previously reported that the U. maydis genome does not harbor an Nmr1 homolog (87), we could identify a gene coding for a protein with an NmrA multidomain. The gene um11107 showed 35% sequence identity to the gene encoding Tar1, a functional Nmr1 homolog of C. neoformans (40). Interestingly, a um11107 knockout mutant did not exhibit the expression of nar1 in the presence of favorable nitrogen sources (unpublished results), indicating that Um11107 does not directly inhibit Nit2 activity.…”
Section: Discussionmentioning
confidence: 96%